Prevention of Pulmonary Fibrosis via Trichostatin A (TSA) in Bleomycin Induced Rats - Ye, Qing; Li, Yanqin; Jiang, Handong; Xiong, Jianfei; Xu, Jiabo; Qin, Hui; Liu, Bin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Purpose: To investigate the effects of non selective histone deacetylase inhibitors Trichostatin A (TSA)on bleomycin-induced pulmonary fibrosis. To investigate the effects of non selective histone deacetylase inhibitors Trichostatin A ( TSA ) on HDAC2, p-SMAD2, HDAC2 mRNA, SMAD2mRNA in pulmonary fibrosis rats and investigate impossible mechanism. Methods: 46 SPF level male SD rats were randomly divided into four groups: ten for normal control group, fourteen for model control group I, twelve for model control group II and ten for treatment group. Rat pulmonary fibrosis was induced by bleomycin(5mg/kg) via single intratracheal perfusion in the two model control groups and treatment group. Normal control mice were instilled with a corresponding volume of 0.9% saline intratracheally. Treatment group was treated by the dilution of TSA 2mg/kg、DMSO 60ul and0.9% saline 1.2ml intraperitoneal injection from the next day ,once a day for three days. Model control group II was treated by the dilution of DMSO 60ul and0.9% saline 1.2ml intraperitoneal injection from the next day once a day for three days. Model control group I and normal control group were treated by 0.9% saline 1.2ml intraperitoneal injection from the next day once a day for three days. All the animals were sacrificed on the 21 day after modeling. The pathological changes were observed by hematoxylin and eosin(HE)stain and masson trichrome stain. The expression of HDAC2 mRNA,SMAD2 mRNA were measured by real-time PCR. The protein level of HDAC2 and p-SMAD2 in serum was measured by Western blot. Results: The pulmonary fibrosis in treatment group were significantly alleviated compared to the two model control groups (P<0.05). Real-time PCR showed that the treatment group had lower expression of lung tissue HDAC2 mRNA than the two model control groups and normal control group (P<0.05). The expression of lung tissue SMAD2 mRNA increased in the two model control groups and treatment group (P<0.05),but there were no significant differences among the three groups(P>0.05). Western blot indicated that the protein level of HDAC2 and p-SMAD2 in serum increased in the two model control groups compared with normal control group(P<0.05).But treatment group had lower protein level of HDAC2 (P<0.05) and no significant difference in the protein level of p-SMAD2 compared to the two model control groups (P>0.05). Conclusion: Non selective histone deacetylase inhibitors of Trichostatin A (TSA) can reduce the bleomycin induced pulmonary fibrosis in rats. TSA attenuates pulmonary fibrosis and it can inhibit HDAC2 expression at the gene and protein level. Bleomycin induced fibrosis has the relationship with p-SMAD2 in gene and protein levels, but TSA inhibit bleomycin-induced lung fibrosis effect with no relation with SMAD2 phosphorylation pathways.